2002
DOI: 10.1002/chin.200219148
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Pyrido[1,2‐a]quinoxalines: Synthesis, Crystal Structure Determination and pH‐Dependent Fluorescence.

Abstract: Pyrido[1,2-a]quinoxalines: Synthesis, Crystal Structure Determination and pH-Dependent Fluorescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…For instance, defective pH regulation of acidic compartments has been observed in human breast cancer cells [19]. Recently, Diwu et al [20] and Duffy et al [21] reported some compounds which are effective as pH dependent fluorescent dye indicators. It would, therefore, be extremely desirable to find a variety of ruthenium(II) complexes which are sensitive to changes in pH in a relevant physiological range, especially in acidic organelles regions.…”
Section: Introductionmentioning
confidence: 97%
“…For instance, defective pH regulation of acidic compartments has been observed in human breast cancer cells [19]. Recently, Diwu et al [20] and Duffy et al [21] reported some compounds which are effective as pH dependent fluorescent dye indicators. It would, therefore, be extremely desirable to find a variety of ruthenium(II) complexes which are sensitive to changes in pH in a relevant physiological range, especially in acidic organelles regions.…”
Section: Introductionmentioning
confidence: 97%
“…As shown in Table 1 and Table S2 , development of pH-sensitive materials for acidic vapors and low-pH aqueous solutions has attracted considerable attention [ 18 , 20 , 22 , 24 , 27 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Many dyes were immobilized according to various strategies, but LB and LS techniques were not used in this field to our knowledge.…”
Section: Resultsmentioning
confidence: 99%
“…Quinoxaline derivatives absorbing the light in the visible region attract great attention as optical sensors. The ability of quinoxalines to change their optical properties when N -heterocycle is protonated was thoroughly investigated to obtain colorimetric and fluorescent pH chemosensors [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ] because these compounds change the color in acidic media with pH < 4 in which many of pH indicators are insensitive [ 28 , 29 , 30 , 31 , 32 ]. Unfortunately, most of the quinoxaline derivatives reported elsewhere in the literature for pH monitoring can be used only in organic solvents or binary solvent mixtures and are inconvenient for real-world analyses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poly‐ N ‐heterocycles have universally been adapted in the exploration of novel biologically sound compounds [ 16 ] due to their wide pharmaceutical activity. Various quinoxaline derivatives show versatile applications like pH‐dependent ultraviolet (UV) and fluorescence characteristics, [ 17 ] antineoplastic activity, [ 18 ] prostaglandin D2 receptor antagonist property, [ 19 ] potent IKK‐2 inhibitor, [ 20 ] potent AChE inhibitor, [ 21 ] vasopressin V2 receptor antagonists and [ 22 ] antibacterial, [ 23 ] antimetabolic [ 24 ] and anticancer activity. [ 25 ] They also extensively exploited as building block for the construction of organic semiconductors [ 26 ] and bioactive spiro compounds.…”
Section: Introductionmentioning
confidence: 99%